Unpacking the theory on ambidexterity: An illustrative case on the managerial architectures, mechanisms and dynamics. Issue 2 (April 2013) - Turner, Neil; Lee-Kelley, Liz
Research on ambidexterity has been focused primarily at the organisational level. There is little in the literature detailing ambidexterity in more complex forms of organising. While much is written on the 'what' of ambidexterity – its enactment has been shown to be beneficial – there is a gap in our understanding of the underlying mechanisms, architectures and dynamics by which organisations can achieve both exploration and exploitation. In this article, we use the lens of intellectual capital to extend current architectural theory. A case study of a project management office in an IT/IS multinational provides the context in which to qualitatively unpack the underpinning intellectual capital architecture, illustrating the interwoven application of human, social and organisational capital in a complicated organisational setting. We reveal the co-existence and mutual interdependence of multiple intellectual capital and process elements, further explaining the 'how' of this increasingly important area of study.